Schema-focused working methods for arts and body-based therapies : a practical guide - Haeyen, Suzanne (New York, NY : Routledge, 2024)
"This book introduces schema-focused working methods for arts and body-based therapies, offering therapists practice-based tools to help their clients strengthen healthy patterns, self-management, and well-being on their path to recovery. Containing over 150 schema-focused working methods for different arts and body-based therapies, such as art therapy, dance therapy, drama therapy, music therapy and body-based or psychomotor therapy, this book offers new ideas and tools for therapists to strengthen their client's adaptive schema modes: the Healthy Adult and the Happy Child. By linking arts and body-based therapies to schema-focused therapy and positive psychology, the goal is to strengthen client's healthy patterns in emotion regulation and establish a healthier well-being. The theoretical framework in the introduction and the scientific evidence for arts and psychomotor therapies, combined with the practice-based examples allows for a text that is broad enough for graduate creative therapy programs and specific enough to serve as a shelf reference for those in practice"--
Keywords: Arts -- Therapeutic use; Mind and body therapies; PSYCHOLOGY / Psychotherapy / General